2001
DOI: 10.1377/hlthaff.20.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Growing Differences Between Medicare Beneficiaries With And Without Drug Coverage

Abstract: Using data from the 1998 Medicare Current Beneficiary Survey (MCBS), we examine changes in beneficiaries' prescription drug coverage from 1997 to 1998 and compare drug use and spending data for beneficiaries with and without drug coverage. The data show that in 1998 the aggregate prescription drug coverage rate of Medicare beneficiaries may have reached a plateau. Also, prescription drug use declined for beneficiaries without drug coverage and increased for those with drug coverage. Covered beneficiaries also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 4 publications
4
55
0
1
Order By: Relevance
“…10 The study herein showed that exceeding the cap for 2.5 to 6 months also affected important medication use and self-reported financial burden from drug costs. The results herein also confirm previous findings that Medicare beneficiaries who are most vulnerable to medication nonuse due to cost include patients with lower incomes, 2,4-6,8 younger age, 6,14,15 and greater number of health problems or poorer health. 4,14,15 We refer readers to Craig et al 15 for greater details and a summary of these studies.…”
Section: Commentsupporting
confidence: 90%
“…10 The study herein showed that exceeding the cap for 2.5 to 6 months also affected important medication use and self-reported financial burden from drug costs. The results herein also confirm previous findings that Medicare beneficiaries who are most vulnerable to medication nonuse due to cost include patients with lower incomes, 2,4-6,8 younger age, 6,14,15 and greater number of health problems or poorer health. 4,14,15 We refer readers to Craig et al 15 for greater details and a summary of these studies.…”
Section: Commentsupporting
confidence: 90%
“…Previous research has also found that regardless of whether they have insurance coverage, elderly women tend to spend more per capita than elderly men do on prescription drugs. 30 …”
Section: Spending Patterns By Selected Servicesmentioning
confidence: 99%
“…1 Approximately ten million Medicare beneficiaries have no prescription drug coverage. 2 Without governmental intervention, this number is likely to grow.…”
Section: R a Pi D Ly R I S I N G P R E S C R I P T I O N D Ru G C O S Tsmentioning
confidence: 99%